2013
DOI: 10.1063/1.4812223
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric, piezoelectric, and dielectric properties of BiScO3-PbTiO3-Pb(Cd1/3Nb2/3)O3 ternary high temperature piezoelectric ceramics

Abstract: Articles you may be interested inEnhanced piezoelectric performance of (0.98-x)Bi(Sc3/4In1/4)O3-xPbTiO3-0.02Pb(Zn1/3Nb2/3)O3 ternary high temperature piezoelectric ceramics (0.95-x)BiScO 3 -xPbTiO 3 -0.05Pb(Cd 1/3 Nb 2/3 )O 3 (BS-xPT-PCN) high temperature piezoelectric ceramics near the morphotropic phase boundary (MPB) have been synthesized by traditional solidstate reaction methods. The microstructural morphology, phase structure, and electrical properties of BS-xPT-PCN ceramics were investigated in detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…On the whole, the x = 0.025/ y = 0.63 sample possesses the optimized comprehensive electromechanical performance with the d 33 of 380 pC/N, k t of 0.51, Q m of 112, and tan δ of 0.010. In order to evaluate the performance achieved in our work, we compared the d 33 and tan δ of our sample with other reported BS-PT ceramic systems, ,,,, as shown in Figure a. A favorable balance between d 33 and tan δ is achieved in our x = 0.025/ y = 0.63 sample, which exhibits advantages compared with other hard-type BS-PT ceramics, making it promising for practical applications.…”
Section: Resultsmentioning
confidence: 90%
“…On the whole, the x = 0.025/ y = 0.63 sample possesses the optimized comprehensive electromechanical performance with the d 33 of 380 pC/N, k t of 0.51, Q m of 112, and tan δ of 0.010. In order to evaluate the performance achieved in our work, we compared the d 33 and tan δ of our sample with other reported BS-PT ceramic systems, ,,,, as shown in Figure a. A favorable balance between d 33 and tan δ is achieved in our x = 0.025/ y = 0.63 sample, which exhibits advantages compared with other hard-type BS-PT ceramics, making it promising for practical applications.…”
Section: Resultsmentioning
confidence: 90%
“…21 Recently, it is also found that adding small amount of ABO 3 end members in BS-PT solid solutions, such as Ba(Sr, Ti)O 3 , LiNbO 3 , LiSbO 3 , Pb(Zn 1=3 Nb 2=3 )O 3 , Pb(Mn 1=3 Nb 2=3 ) O 3 , and Pb(Sc 1=2 Nb 1=2 )O 3 are able to increase the piezoelectric constant up to 500 pC/N. [38][39][40][41][42][43][44] However, the ABO 3 end members will decrease the Curie temperature obviously. Wang et al found that the BS-PT ceramics derived from two-step method has a large d 33 value of 700 pC/N with slightly decreased Curie temperature of 446 C. 45,46 The enhanced piezoelectric properties may result from the fine grain, which indicates small domain structure in the BS-PT ceramics.…”
Section: Electric Properties Of Bs-pt Ceramicsmentioning
confidence: 99%
“…Ferro‐/piezo‐electric materials are a special class of functional materials which achieve the interconvertibility between the mechanical energy and the electrical energy, and have been subject to widespread applications in modern electronic devices, actuators and sensors . Although nowadays Pb‐based (PbZr x Ti 1− x O 3 , PZT) ceramics have been widely used, their development and applications are hampered because of low Curie temperatures ( T C ) . In addition, many piezoelectric ceramics display higher piezoelectric coefficient d 33 and electromechanical coupling properties than PZT, but too low T C is also a major obstacle to their applications, such as Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 (PMNT, T C ~ 130°C), Pb(Zn 1/3 Nb 2/3 )O 3 ‐PbTiO 3 (PZNT, T C ~ 160°C), Ba x Ca 1− x Zr y Ti 1− y O 3 ( T C ~ 90°C, T r‐t ~ 40°C).…”
Section: Introductionmentioning
confidence: 99%